2021
DOI: 10.1002/ppsc.202000316
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Spectroscopic Probes for Structures and Processes at the Surface of Noble Metallic Nanoparticles

Abstract: of molecules and the dynamic interactions between molecules and metallic NPs is challenging owing to the requirement of real-time, in situ, and nondestructive surface probing technologies. This review presents an overview of probing the structures and dynamic processes of molecules on the surface of metallic NPs by different spectroscopic techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 252 publications
(370 reference statements)
0
5
0
Order By: Relevance
“…93,94 Unlike most spectroscopic methods, SHS is able to differentiate photon signals that are radiated by molecules in aqueous solutions and ligands on particle surfaces. 95 A study by Das et al 93 shows promise for SHS as a spectroscopic method for determining the equilibrium binding of NP with proteins. SHS is also a beneficial tool for sensing applications because of the enhanced resonance seen when either the fundamental or harmonic wavelengths are closely tuned to their localized surface plasmon resonance.…”
Section: K Pmentioning
confidence: 99%
See 1 more Smart Citation
“…93,94 Unlike most spectroscopic methods, SHS is able to differentiate photon signals that are radiated by molecules in aqueous solutions and ligands on particle surfaces. 95 A study by Das et al 93 shows promise for SHS as a spectroscopic method for determining the equilibrium binding of NP with proteins. SHS is also a beneficial tool for sensing applications because of the enhanced resonance seen when either the fundamental or harmonic wavelengths are closely tuned to their localized surface plasmon resonance.…”
Section: K Pmentioning
confidence: 99%
“…Second harmonic light scattering (SHS) is a nonlinear optical process that combines intrinsic surface specificity with a scattering detection geometry to probe nanoparticles in situ . It has been employed for a variety of uses including measuring free energies of adsorption, surface protein adsorption, the binding affinity of protein adsorption kinetics, the molecular structure, and reaction rates of biological cells. , Unlike most spectroscopic methods, SHS is able to differentiate photon signals that are radiated by molecules in aqueous solutions and ligands on particle surfaces . A study by Das et al shows promise for SHS as a spectroscopic method for determining the equilibrium binding of NP with proteins.…”
Section: Spectroscopic Techniques and Theoretical Models To Investiga...mentioning
confidence: 99%
“…Nuriya et al synthesized a SHG-specific dye (AP3) that exhibited desirable SHG intensity on the cell membrane with virtually no TPF signal . Then, AP3 was used in multimodal multiphoton imaging with coupling of sum-frequency generation and coherent anti-Stokes Raman scattering to detect the characteristics of lipid bilayers in giant vesicles and living cells. , SHG is a second-order nonlinear coherent scattering process in which two photons with optical frequency ω are converted to a single photon with an optical frequency of 2ω after interacting with nonlinear optical (NLO) materials. ,, Therefore, the SHG process enables a redshift of the laser wavelength into the infrared window, allowing high-resolution deep-tissue imaging. …”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49] Additionally, TPL was also demonstrated to be powerful for analyzing the surface structures and dynamics of nanoparticles. [50][51][52][53][54][55] It was demonstrated that the combination of SHG and TPL could provide rich information to reveal the detailed surface processes on nanoparticles. For instance, SHG and TPL emission from AgNPs were used to analyze the molecular adsorption and elimination of surface defects on AgNPs.…”
Section: Introductionmentioning
confidence: 99%